Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1192/pb.24.6.218
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cosmetic surgery and ‘DIY’ surgery in patients with body dysmorphic disorder

Abstract: Aims and MethodLittle is known about the outcome of cosmetic surgery in patients with body dysmorphic disorder (BDD). Self-reported outcome was collected on 25 patients with BDD who at the time of psychiatric assessment had reported that they had had cosmetic surgery in the past.ResultsTwenty-five patients with BDD had a total of 46 procedures. The worst outcome was found in those who had had rhinoplasty and those with repeated operations. Mammoplasty and pinnaplasty was associated with higher degrees of satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 7 publications
5
78
0
10
Order By: Relevance
“…Our results reveal that patients with BDD have significantly lower preoperative and postoperative satisfaction of their noses as measured by the ROE instrument as compared to those without BDD. This is in accordance with the small number of studies that also investigated the role of BDD on outcome [5][6][7]. Picavet et al also used the ROE instrument in their study and demonstrated that patients with moderate to severe body dysmorphic disorder symptoms scored their postoperative satisfaction significantly lower compared with patients with no or mild symptoms [6].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our results reveal that patients with BDD have significantly lower preoperative and postoperative satisfaction of their noses as measured by the ROE instrument as compared to those without BDD. This is in accordance with the small number of studies that also investigated the role of BDD on outcome [5][6][7]. Picavet et al also used the ROE instrument in their study and demonstrated that patients with moderate to severe body dysmorphic disorder symptoms scored their postoperative satisfaction significantly lower compared with patients with no or mild symptoms [6].…”
Section: Discussionmentioning
confidence: 51%
“…Studies from psychiatric literature reveal that the majority of BDD patients experienced no improvement or even worsening of BDD symptoms after surgery [5]. Although some studies have attempted to investigate the impact of BDD on level of satisfaction after nose surgery [5][6][7], most of them did not use proper validated instruments specific for rhinoplasty to measure outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethicists have coined the term, 'knowledge framing', to describe desirable treatment effects arising from proper presentation of information to patients during the clinical encounter, distinct from the placebo (unwanted) effect in clinical trials. 10 Whilst debate rages about whether it is permissible to harness the placebo effect to treat psychogenic disease, few would condone placebo use to treat organic diseases for which appropriate therapy is available. Purists maintain that any practice involving deceit of patients is inappropriate, and that they must be informed of the inert nature of the placebo when it is administered.…”
mentioning
confidence: 99%
“…There is frequent comorbidity in BDD with depression, a significant risk of suicide 4,5 and dissatisfaction with cosmetic surgery. 6,7 The authors make a number of recommendations for treatment with pimozide (an anti-psychotic drug) which is not evidence based. There have been two randomised controlled trials of serotonin reuptake inhibitor with BDD.…”
mentioning
confidence: 99%